The inter-association task force for preventing sudden death in secondary school athletics programs: best-practices recommendations - Casa, D. J.; Almquist, J.; Anderson, S. A.; Baker, L.; Bergeron, M. F.; Biagioli, B.; Boden, B.; Brenner, J. S.; Carroll, M.; Colgate, B.; Cooper, L.; Courson, R.; et al. (Journal of Athletic Training, 2013)
This document provides a roadmap for policy considerations regarding health and safety concerns for secondary school athletes. Although these guidelines are not exhaustive for all conditions, these best practices address the leading causes of sudden death in this population (head and neck injuries, exertional heat stroke [EHS], sudden cardiac arrest [SCA], and exertional sickling). Further, we present information to address the infrastructure conditions and barriers that can introduce the most risk to athletes (lack of emergency action plans [EAPs], lack of medical staff, lack of emergency equipment [eg, defibrillators], poor heat acclimatization policies, and improper conditioning sessions).